Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1161/01.atv.11.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced constriction of the peripheral large artery in response to acute induction of a low-flow state in human hypercholesterolemia.

Abstract: The diameter, blood velocity, and blood flow of the brachial artery were evaluated with a pulsed-Doppler apparatus before and after wrist occlusion in 16 normocholesterolemic and 27 hypercholesterolemic male subjects of similar age and body mass index. Before occlusion, no hemodynamic differences were observed between the two groups. Occlusion significantly reduced blood velocity and blood flow in the two groups (p< 0.001), but such reductions were not different between hypercholesterolemic and normocholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
(16 reference statements)
5
16
0
Order By: Relevance
“…There is some evidence that impaired vascular function in the radial artery is associated with diminished L-FMC responses, 1,3 whereas brachial artery L-FMC may be increased in subjects with risk factors or coronary disease. 5,21,22 Our findings are in broad agreement with previous studies of the radial artery, 1,3 but contrast with those in the brachial artery, reinforcing a previous suggestion of arterial site specificity in vasoconstrictor function. 4 Furthermore, the impact of coronary catheterization on systemic conduit artery This study had a number of limitations.…”
Section: Discussionsupporting
confidence: 91%
“…There is some evidence that impaired vascular function in the radial artery is associated with diminished L-FMC responses, 1,3 whereas brachial artery L-FMC may be increased in subjects with risk factors or coronary disease. 5,21,22 Our findings are in broad agreement with previous studies of the radial artery, 1,3 but contrast with those in the brachial artery, reinforcing a previous suggestion of arterial site specificity in vasoconstrictor function. 4 Furthermore, the impact of coronary catheterization on systemic conduit artery This study had a number of limitations.…”
Section: Discussionsupporting
confidence: 91%
“…However, in this group of patients mean total cholesterol and LDL levels were rather high and the study population also contained patients with cardiovascular complications, including hypertension. Data in the literature have shown that, in the brachial artery, diameter and blood flow were no different in normocholesterolaemic subjects than in patients with hypercholesterolaemia, although the arterial diameters tended to be somewhat larger in the hypercholesterolaemic group [34]. In the latter study it was suggested that cholesterol probably does not influence the arterial circulation under basal conditions, but might be still able to alter large artery reactivity.…”
Section: Discussionmentioning
confidence: 73%
“…Arterial diameters of the CCA and FA were slightly larger in IDDM patients. During the early stages of atherosclerotic disease, arterial diameter may indeed become increased (33,34). Since the CCA and FA, in contrast to the BA, are most prone to atherosclerosis in diabetic patients, the presence of early (still below the detection limit of B-mode scanning) atherosclerosis cannot be excluded.…”
Section: Results-mentioning
confidence: 99%